PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT EVALUASI KINERJA PT. GUNUNG SELAMAT LESTARI LABUHAN BATU SELATAN - METYRIA IMELDA HUTABARAT (LP2MTBM MAKARIOZ, 2020)
This study aims to determine the application of accountability accounting and how far the effect on managementperformance as an evaluation tool at PT. Gunung Selamat Lestari Labuhan Batu Selatan in 2017 and 2018. The researchmethod used in this study consisted of the location of the research that was used as the place for this research was at PT.Gunung Selamat Lestari, which is located on the Cross-Sumatra Road Village, Tolan Week. The types and sources of dataused in this study are secondary data. Secondary data used are budget and realization in 2017 and 2018. The researchvariables used in this study are independent variables and dependent variables, namely accountability accounting andmanagement performance evaluation. Data collection methods used in this study are library methods and field methods.While the data analysis method used in this study is using descriptive methods. Based on the discussion and analysis ofdata, it can be concluded that PT. Gunung Selamat Lestari has implemented accountability accounting but not fully. Theapplication of accountability accounting in the preparation of budgets that have involved all parts, and the preparation of aclearly visible organizational structure. Reporting on budget realization in the company is an accountability and an evaluationmaterial for the manager who compiles the realization report on the costs he manages, the realization report contains thebudget, realization, and deviation of each element.